To survive ... with Yakan grace [videorecording] - Medina, Susan Calo; Quintos, Floy (Travel Time, 1996)
The Yakans of Basilan have proven that theirs is a culture that struggles on in the face of tremendous odds through their music, dance, art, costume and adornments.